DER BEITRAG VON VERNETZTEN STUDIENINHALTEN ZU EINER GANZHEITLICHEN THEOLOGISCHEN AUSBILDUNG - B. Stengel (Acta Theologica)
„Ganzheitliche theologische Ausbildung” (holistic theological education) means that, in addition to learning specialist knowledge, students are enabled to reflect and promote their own spirituality with the goal of being able to act on the basis of knowledge combined with a Christ-oriented life and ministry in the church. This article explains that the networking of course content from the various subject areas of theology makes an important contribution to this goal. At the same time, however, it becomes clear that this networking at theological seminaries and colleges in German-speaking countries is only implemented very slowly or even completely refused. The author names the reasons for this and makes specific suggestions as to how a networking of course content can be implemented. He does this in the following way: To begin with, the author presents how, in the current theological as well as didactic-pedagogical debate, a holistic approach of networking subject areas and course contents is considered to be important for theological education. Secondly, based on the findings of the author´s research it is attempted to show, outlining a variety of reasons, that as far as the practice of theological education is concerned there is substantial resistance to the idea of networking subject areas. Thirdly, suggestions are made on how to implement a targeted and meaningful networking of study content. Finally, the role of teachers in this process is examined. With their role model and an adequate understanding of mentorship, they have an important influence on the way that students can network course content in a meaningful and purposeful manner.